Cultural influences and mandated counseling in Malaysia - Abu Talib, Mansor (Canadian Center of Science and Education, 2010)
It is unfair to conclude that Western and Eastern differences have caused conflict in the practice of counselling, especially in mandated counselling. It is reasonable to assume that without the Western approach and understanding of counselling, the East would still be unable to develop their own theory of helping. How then does one compare different approaches? Such an assessment can be argued clearly from a cultural perspective as in the case of mandated counselling. This paper discusses the influence of culture which has shaped the practice of mandated counselling and the appropriate practice of mandated counselling in a Malaysian setting. Many of the points discussed here are drawn from the data informed by seven informants in a research entitled ‘Mandated Counselling In Malaysia: A Heuristic Phenomenological Inquiry Of Involuntary Participation’. The phenomenon of counselling as originated and practised in the West, which has served as the significant model for the Malaysian style of counselling, is discussed. The concept of guidance and crisis intervention in counselling as practised in Malaysia has shaped the appropriate acceptance of mandated counselling. Respect for authority, a need to ‘save face’, directives from the authority and the values of we-ness makes mandated counselling in a Malaysian setting a relevant intervention.